(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Confirmation formation plays an important role in helping children and adolescents develop faith maturity within the Catholic Church. However, in practice, confirmation formation is often administrative in nature and less connected to participants’ lived faith experiences. This community service activity aimed to improve participants’ understanding of faith, spiritual awareness, and active involvement through a contextual and participatory confirmation formation model. The activity employed a descriptive qualitative approach supported by simple quantitative data through pre-test and post-test assessments. Data were collected through observation, interviews, and participant evaluations involving 30 children and adolescents aged 12–17 years at Santa Maria Immaculata Lewolaga Parish. The results indicate a clear improvement in participants’ understanding of faith, reflected in the increase of average scores from 48% in the pre-test to 86% in the post-test. Participants also showed greater confidence in expressing opinions, stronger engagement in discussions, and more active participation in liturgical activities. In addition, the activity contributed positively to strengthening youth pastoral formation within the parish community. These findings suggest that contextual and participatory formation approaches are effective in supporting faith maturity among children and adolescents and can be further developed in parish-based pastoral ministry.